Pengaruh Kepercayaan, Kepuasan Pelanggan dan Citra Perusahaan terhadap Loyalitas Pelanggan pada MG Store Padang - Marlius, Doni; Wulandari, Vici (Lembaga Yasin AlSys, 2025)
The purpose of this research is to see whether Trust has an effect on Customer Loyalty at the Mg Store Padang shop and whether Customer Satisfaction has an effect on Customer Loyalty at the Mg Store Padang shop and whether Company Image has an effect on Customer Loyalty at the Mg Store Padang shop. This type of research uses quantitative methods, collecting data through distributing questionnaires to 96 respondents using accidental sampling techniques, namely non-probability sampling techniques. By using instrument tests (validity test and reliability test), classical assumption tests (normality test, multicollinearity test and heteroscedasticity test) then multiple linear regression and hypothesis testing with the help of the SPSS application. The results of the research show that Trust, Customer Satisfaction and Company Image have a positive and significant effect on Customer Loyalty.